RANCANG BANGUN SISTEM INFORMASI PENJUALAN BERBASIS WEBSITE (STUDI KASUS : MITRA SINAR JAYA) - Rasmawati, (2022)
Sales information systems have an important role in a company engaged in sales, because sales information systems have a goal to support the development of an ongoing business process. Mitra Sinar Jaya is a company engaged in sales. Sales transaction activities that take place at Mitra Sinar Jaya are still carried out offline. Not only that, Mitra Sinar Jaya has also not carried out the data collection process for goods that have been sold, resulting in the seller not knowing the sales report every month. This study has a goal to design a web-based sales information system at Mitra Sinar Jaya. The system development method that will be used in this research is the waterfall method. With the design of this sales information system, it is hoped that Mitra Sinar Jaya can improve the quality of service to customers and can manage sales reports every month.